GAMBARAN DUKUNGAN MASYARAKAT TERHADAP KELUARGA YANG MEMILIKI ANAK AUTIS - Era Era; Jumaini Jumaini; Reni Zulfitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2021)
Families of autistic children face challenges that put them at high risk of stress, community support can reduce the negative impact of stress, this is because with the support of the community the family of autistic children feel themselves not alone in caring for autistic children, feel motivated in caring for autistic children, and more comfortable in the community environment. So that this community support is needed in providing care and acceptance from the family of autistic children. The purpose of this research is to identify the description of community support for families with autistic children. Quantitative with descriptive research design. This research was conducted in the Limbungan village area with a sample of 99 respondents. The measuring instrument used is a questionnaire with 26 questions consisting of 4 main components, namely informational, emotional, reward, and instrumental support which has been tested for validity and reliability. The analysis used is univariate analysis to describe community support for families with autistic children. the majority of the age of late adolescent respondents (26.3%) and early adulthood is (26.3%), most of the gender is 52 people (52.5%), most Muslims are 92 people (92.9%), most undergraduate education is 29 people (29.3%), most Malays are 41 people (41.4%). And get an average of good community support of 56 people (56.6%). The results of this study advise the community to provide support to the families of autistic children so that families are motivated. Keywords: Autistic Children, Community Support, Family